Cellulose-assisted combustion synthesis of functional materials for energy storage or conversion - Cai, R.; Zhou, W.; Shao, Zongping (Bentham Science Publishers Ltd., 2010)
Combustion synthesis has attracted considerable attention recently for its advantages of low processing cost, high energy efficiency, and high production rate. This chapter presents the preparation of functional oxide materials for energy storage or conversion by cellulose-assisted combustion synthesis. In traditional solid-solution-phase combustion synthesis, e.g., the glycine-nitrate process (GNP), a great quantity of gas is evolved during the synthesis, which can create large amounts of ash by blowing away the products. Natural cotton fibers with a hierarchical pore structure were used as a micro-reactor for the GNP in this study. This novel process is environmentally friendly. Furthermore, the resulting particle size was smaller, which was attributed to the blocking effect of cellulose on inter-particle contact during the synthesis. The method was applied for the synthesis of samaria-doped ceria (SDC) as an electrolyte for solid-oxide fuel cells (SOFCs). SDC powder with a particle size as small as 10 nm was obtained, which was easily sintered to form a dense electrolyte at 1350 oC, several hundred degrees lower than that prepared from the traditional solid-state reaction. La0.6Sr0.4Co0.2Fe0.8O3 perovskite oxide was also prepared and showed higher purity and better cathode performance in SOFCs than that prepared by a sol-gel process. By adopting the same method, phase-pure spinel Li4Ti5O12 could be synthesized at 700 oC. The resulting powder had an excellent rate performance in secondary lithium-ion batteries, with a capacity of 140 mAh g-1 even at a 10 C discharge rate. More importantly, solid TiO2 oxides can also be utilized as the raw materials for this synthesis, making the process highly cost-attractive. © 2010 Bentham Science Publishers Ltd. All rights reserved.